Building the Smart City: Leipzig. - Korzer, Tanja; Ginzel, Beate; Riedel, Nadja (Springer, 2018)
Leipzig is one of the most dynamic cities in Eastern Germany, with approximately 580,000 inhabitants. After years of population decline and above-average unemployment rates, Leipzig has started to regain popularity in recent years. The number of inhabitants is continuously increasing. Population forecasts anticipate up to 720,000 inhabitants by the year 2030. Leipzig s economy is successfully turning from a post-industrial to a modern, knowledge-based structure.In 2015, the city joined the HORIZON 2020 Smart city and communities project TRIANGULUM (www.triangulum-project.eu) as a Follower City. This was the starting point for a Smart City strategy for the City of Leipzig. The municipality is developing a Smart City implementation strategy by means of a broad participation process, involving the municipal utilities, the scientific institutions and the civil society. The case study is Leipzig West, a former industrialized area which has been turned into a lively and attractive neighborhood in recent years. The area has been one of the main focus areas for urban regeneration processes during its years of decline and high vacancy rates. With the help of national and EU subsidies the district became a role model for similar neighborhoods in Leipzig. Now, it will take on this role once again as it becomes the first district in Leipzig to develop a Smart City strategy.This article summarizes the current project activities. Special focus will be put on the governance structures that have been established and the co-creation processes between different stakeholders for the elaboration of the Smart City implementation strategy for Leipzig West.
Keywords: Stadtentwicklungsplanung; Partizipation; Wirtschaftsentwicklung; Bevölkerungsentwicklung; Smart City; Wirtschaftsstandort; Governance; Fallbeispiel